PLATFORMS AS EPISTEMIC INFRASTRUCTURES: MEASUREMENTS, DATA FANDOMS PRACTICES AND THE RECONFIGURATION OF MUSIC CHARTS - d’Andréa, Carlos Frederico de Brito; Santos Dias, Natália (AoIR Selected Papers of Internet Research, 2026)
This study examines online platforms as epistemic infrastructures, focusing on how they shape knowledge production through its data-oriented ways of tracking, measuring, and governing collective practices. Using the reconfiguration of music charts as a case study, the article analyzes how data fandoms tactically influence the measurements and the visibility of success, revealing tensions between cultural industries, participatory cultures and platform governance. Through this lens, the article argues that platforms function as pivotal infrastructures that not only expand the volume and diversity of metrics attached to the rankings, but also make possible a fan culture in which the relationship with music is centrally mediated by measurable interactions. In this sense, platforms act as epistemic infrastructures in which governance of numbers is under dispute by multiple actors who can manipulate indicators and policies, thereby asserting emerging forms of knowledge.